2018
DOI: 10.3389/fmicb.2018.00884
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Two Lpp20 CD4+ T Cell Epitopes in Helicobacter pylori-Infected Subjects

Abstract: Antigen-specific CD4+ T cells play an essential role in effective immunity against Helicobacter pylori (H. pylori) infection. Lpp20, a conserved lipoprotein of H. pylori, has been investigated as one of major protective antigens for vaccination strategies. Our previous study identified two H-2d-restricted CD4+ T cell epitopes within Lpp20 and an epitope vaccine based on these epitopes was constructed, which protected mice in prophylactic and therapeutic vaccination against H. pylori infection. Immunodominant C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…A similar predominant Th1 response was observed early in rhesus macaques during acute H. pylori infection (Mattapallil et al, 2000). Several research groups including our team demonstrated that immunodominant CD4 + epitopes of some H. pylori antigens induced a Th1-skewed response in humans (Chen et al, 2013;Yang et al, 2013;Ning et al, 2018). Taken together, these results highlight a vigorous Th1 immune response against H. pylori infection.…”
Section: Introductionsupporting
confidence: 75%
“…A similar predominant Th1 response was observed early in rhesus macaques during acute H. pylori infection (Mattapallil et al, 2000). Several research groups including our team demonstrated that immunodominant CD4 + epitopes of some H. pylori antigens induced a Th1-skewed response in humans (Chen et al, 2013;Yang et al, 2013;Ning et al, 2018). Taken together, these results highlight a vigorous Th1 immune response against H. pylori infection.…”
Section: Introductionsupporting
confidence: 75%
“…The highly conserved H pylori Lpp20 lipoprotein was previously shown to induce protection against H pylori infection in mice. 31 Ning et al 32 identified two immunodominant epitopes within H pylori Lpp20 that were able to stimulate the proliferation of CD4 + T cells from H pylori-infected subjects. Whether these epitopes confer protective immunity is, however, unclear.…”
Section: Selection Of Novel Protective Antigens and Epitopesmentioning
confidence: 99%
“…HP-IgG-Ab is an immunoglobulin which can be used to diagnose H. pylori infection. , It could be seen from Figure that the content of HP-IgG-Ab of Group HP was statistically significant higher compared with that of Group C. This revealed that H. pylori induced the secretion of IgG-Ab antibodies.…”
Section: Resultsmentioning
confidence: 86%